PEMBELAJARAN IPS TERPADU DI SEKOLAH MENENGAH PERTAMA - Echanudin, Jarwanto (MIIPS, 2008)
In this time social science curriculum for the Junior High School have united all social science in one study discipline. Integrated study model is one of suggested curriculum implementation model for the application of . Through integrated study, the participant educated can obtain direct experience, so that can add strength to accept, save and produce impressions about studied things .The study of integrated approach is study eliminating boundary various subject in the form of entirety or unit. The study of integrated social science is taught by team where one topic of studied is done by more than a teacher. Every teacher will have each duty as according to agreement and membership